Abnormal Right-Hemispheric Sulcal Patterns Correlate with Executive Function in Adolescents with Tetralogy of Fallot. (3rd May 2021) - Morton, Sarah U; Maleyeff, Lara; Wypij, David; Yun, Hyuk Jin; Rollins, Caitlin K; Watson, Christopher G; Newburger, Jane W; Bellinger, David C; Roberts, Amy E; Rivkin, Michael J; Grant, P Ellen; Im, Kiho
Abstract: Neurodevelopmental disabilities are the most common noncardiac conditions in patients with congenital heart disease (CHD). Executive function skills have been frequently observed to be decreased among children and adults with CHD compared with peers, but a neuroanatomical basis for the association is yet to be identified. In this study, we quantified sulcal pattern features from brain magnetic resonance imaging data obtained during adolescence among 41 participants with tetralogy of Fallot (ToF) and 49 control participants using a graph-based pattern analysis technique. Among patients with ToF, right-hemispheric sulcal pattern similarity to the control group was decreased (0.7514 vs. 0.7553, P  = 0.01) and positively correlated with neuropsychological testing values including executive function ( r  = 0.48, P  < 0.001). Together these findings suggest that sulcal pattern analysis may be a useful marker of neurodevelopmental risk in patients with CHD. Further studies may elucidate the mechanisms leading to different alterations in sulcal patterning.